Development with dignity self-determination, localization, and the end to poverty - Palmer, Tom G.; Warner, Matt (Rethinking development, 2022)
"At a time when the global development industry is under more pressure than ever before, this book argues that an end to poverty can only be achieved by prioritising human dignity. Unable to adequately account for the roles of culture, context, and local institutions, today's outsider-led development interventions continue to leave a trail of unintended consequences, ranging from wasteful to even harmful. This book shows that increased prosperity can only be achieved when people are valued as self-governing agents. Social orders that recognize autonomy and human dignity unleash enormous productive energy. This in turn leads to the mobilization of knowledge sharing that is critical to innovation and localized problem solving. Offering a wide range of interdisciplinary perspectives and specific examples from the field showing these ideas in action, this book provides NGOs, multilateral institutions and donor countries with practical guidelines for implementing "dignity-first" development. Compelling and engaging, with a wide range of recommendations for reforming development practice and supporting liberal democracy, this book will be an essential read for students and practitioners of international development"--